2012
DOI: 10.1080/14786419.2010.531016
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects ofOcimum sanctumon lipid peroxidation and antioxidant status in streptozocin-induced diabetic rats

Abstract: The antioxidant effects of Ocimum sanctum in experimental streptozocin-induced diabetic rats was evaluated in this study. Streptozocin, 55 mg kg(-1) body weight, was injected intraperitoneally once daily for 30 days to induce diabetes mellitus in rats. Streptozocin-induced diabetic rats were orally treated with an aqueous extract of O. sanctum once daily for 30 days. After the experimental period, thiobarbituric acid reacting substances (TBARS) and antioxidant enzymes such as catalase, superoxide dismutase (SO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Totally different elements of the planthistorically have been used in Ayurveda and Siddha systems for the treatment of various ailments such as infection, skin diseases and hepatic disorders, and as an antidote for snake and scorpion stings. This plant is suggested for human monocyte (THP‐1) cell activation (Choudhury et al, ), influenza virus (H1N1) (Jadhav et al, ), anti‐plasmodial activity (Rajendran et al, ), anti‐inflammatory, gastrointestinal and hepatoprotective effects (Lahon and Das, ; Kamyab and Eshraghian, ), neuroprotective activity (Venuprasad et al, ), anti‐ageing, anti‐stress and reactive‐oxygen‐species scavenging activity (Pandey et al, ), chemopreventative activity (Baliga et al, ; Bhattacharyya and Bishayee, ), human pancreatic cancer cell (Shimizu et al, ), mutagenic potential (Chandrasekaran et al, ), stress‐induced anxiety (Bathala et al, ), stress‐induced central monoaminergic and oxidative changes in rats (Ahmad et al, ), fatigue stress (Zamin, ), typhoid fever (Mandal et al, ), cerebral ischaemia/reperfusion (Ahmad et al, ), anti‐dengue activity (Tang et al, ), ameliorative activity (Mahaprabhu et al, ), lipid lowering and anti‐oxidant activity (Suanarunsawat et al, ), cognitive disorders (Giridharan et al, ), anti‐diabetic activity (Patil et al, ; Muralikrishnan et al, ), thrombolytic activity (Khan et al, ), effect on sperm count and reproductive hormones (Sethi et al, ), anti‐melanoma and radioprotective activity (Monga et al, ), anti‐hyperlipidaemic and cardio‐protective activity (Panda and Naik, ; Suanarunsawat et al, ), anxiety and depression (Tabassum et al, ; Chatterjee et al, ), leishmanicidal activity (Suzuki et al, ) and immune response (Mediratta et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Totally different elements of the planthistorically have been used in Ayurveda and Siddha systems for the treatment of various ailments such as infection, skin diseases and hepatic disorders, and as an antidote for snake and scorpion stings. This plant is suggested for human monocyte (THP‐1) cell activation (Choudhury et al, ), influenza virus (H1N1) (Jadhav et al, ), anti‐plasmodial activity (Rajendran et al, ), anti‐inflammatory, gastrointestinal and hepatoprotective effects (Lahon and Das, ; Kamyab and Eshraghian, ), neuroprotective activity (Venuprasad et al, ), anti‐ageing, anti‐stress and reactive‐oxygen‐species scavenging activity (Pandey et al, ), chemopreventative activity (Baliga et al, ; Bhattacharyya and Bishayee, ), human pancreatic cancer cell (Shimizu et al, ), mutagenic potential (Chandrasekaran et al, ), stress‐induced anxiety (Bathala et al, ), stress‐induced central monoaminergic and oxidative changes in rats (Ahmad et al, ), fatigue stress (Zamin, ), typhoid fever (Mandal et al, ), cerebral ischaemia/reperfusion (Ahmad et al, ), anti‐dengue activity (Tang et al, ), ameliorative activity (Mahaprabhu et al, ), lipid lowering and anti‐oxidant activity (Suanarunsawat et al, ), cognitive disorders (Giridharan et al, ), anti‐diabetic activity (Patil et al, ; Muralikrishnan et al, ), thrombolytic activity (Khan et al, ), effect on sperm count and reproductive hormones (Sethi et al, ), anti‐melanoma and radioprotective activity (Monga et al, ), anti‐hyperlipidaemic and cardio‐protective activity (Panda and Naik, ; Suanarunsawat et al, ), anxiety and depression (Tabassum et al, ; Chatterjee et al, ), leishmanicidal activity (Suzuki et al, ) and immune response (Mediratta et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…[28] Administration of OS to streptozocin-induced diabetic rats for 30 days significantly reduced the plasma level of TBARS and improved the status of the antioxidant enzymes catalase, SOD and GPx in vital organs such as the liver and kidney. [29] Similarly, aqueous extract OS L is sued for management of diabetes and related complications [30,31] (while methanolic extract of OS Linn. reverses dyslipidemia and oxidative stress in alloxan induced type I diabetic rat model.…”
Section: Antidiabeticmentioning
confidence: 99%
“…It was reported that the leaves of this plant contain hydroalcoholic extract which is responsible for the antioxidant property. When the leaves of O. sanctum were provided with streptozocin-induced diabetic rats for 30 days, it was found to improve the activity of antioxidant enzyme catalase and reduce the plasma level of thiobarbituric acid in the vital organs like kidneys and liver [54].…”
Section: Anti-oxidantmentioning
confidence: 99%